KETERLIBATAN ORANG TUA DALAM PENGENALAN SEKS PADA ANAK USIA DINI - Ria Fransisca; Yuliani Eka Putri (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The introduction of sex in early childhood is very important to implement because introducing sex must be done as early as possible. Many people think that sex education at an early age is not yet the time to be introduced to children, and the desire for sex is usually only introduced to the extent of the child???s gender as a boy or girl. This article contains a literature review on the introduction of sex in early childhood. Sources of research data were taken from several document in the form of books and journals from previous research results that were relevant to this research. By introducing sex to children at an early age, it can increase parents awareness of introcuding sex from an early age that is appropriate to the stages of child development.